Cost-Effectiveness Evaluations of Psychological Therapies for Schizophrenia and Bipolar Disorder: A Systematic Review. (22nd July 2019) - Shields, Gemma Elizabeth; Buck, Deborah; Elvidge, Jamie; Hayhurst, Karen Petra; Davies, Linda Mary
Abstract: Objectives: This review aims to assess the cost-effectiveness of psychological interventions for schizophrenia/bipolar disorder (BD), to determine the robustness of current evidence and identify gaps in the available evidence. Methods: Electronic searches (PsycINFO, MEDLINE, Embase) identified economic evaluations relating incremental cost to outcomes in the form of an incremental cost-effectiveness ratio published in English since 2000. Searches were concluded in November 2018. Inclusion criteria were: adults with schizophrenia/BD; any psychological/psychosocial intervention (e.g., psychological therapy and integrated/collaborative care); probability of cost-effectiveness at explicitly defined thresholds reported. Comparators could be routine practice, no intervention, or alternative psychological therapies. Screening, data extraction, and critical appraisal were performed using pre-specified criteria and forms. Results were summarized qualitatively. The protocol was registered on the PROSPERO database (CRD42017056579). Results: Of 3, 864 studies identified, 12 met the criteria for data extraction. All were integrated clinical and economic randomized controlled trials. The most common intervention was cognitive behavioral therapy (CBT, 6/12 studies). The most common measure of health benefit was the quality-adjusted life-year (6/12). Follow-up ranged from 6 months to 5 years. Interventions were found to be cost-effective in most studies (9/12): the probability of cost-effectiveness ranged from 35-99.5 percent. All studies had limitations and demonstrated uncertainty (particularly related to incremental costs). Conclusions: Most studies concluded psychological interventions for schizophrenia/BD are cost-effective, including CBT, although there was notable uncertainty. Heterogeneity across studies makes it difficult to reach strong conclusions. There is a particular need for more evidence in the population with BD and for longer-term evidence across both populations.